Association between physical activity and clinical outcomes in high-risk hypertension: Post-hoc analysis of SPRINT - Richard Kazibwe; Matthew J. Singleton; Parag A. Chevli; Arnaud D. Kaze; Juliana H. Namutebi; Michael D. Shapiro; Joseph Yeboah (Elsevier, 2023)
Objective: Engaging in physical activity (PA) is recommended to reduce the risk of morbidity and mortality in patients with hypertension. However, the association between PA and clinical outcomes in individuals with high-risk hypertension is understudied. We examined the relationship between PA and clinical outcomes in the Systolic Blood Pressure Intervention Trial (SPRINT). SPRINT investigated the benefit of intensive (vs. standard) blood pressure treatment in patients with high-risk hypertension. Methods: Baseline data on PA was self-reported. Vigorous-intensity PA (VPA) was categorized into 2 groups based on frequency of "Rarely or Never" and 1 or more sessions/month. Moderate-intensity PA (MPA) was also categorized into 2 groups based on average duration/day of <15 min and 15 or more minutes. Using multivariable Cox regression, we estimated the associations between PA the primary outcome which was a composite of cardiovascular events, and all-cause mortality. Results: A total of 8,320 (age 67.8 ± 9.3, 34.9% women) of SPRINT participants with data on PA were included. During a median follow-up of 3.8 years, 619 primary outcome, and 419 all-cause mortality events occurred. Compared to not engaging in VPA, the risk of the primary outcome, myocardial infarction, and all-cause mortality (HR 95% CIs) associated with VPA of ≥1sessions/month was 0.79(0.65-0.94; p=0.009), 0.70(0.52-0.93; p=0.014) and 0.75(0.60-0.94; p=0.011), respectively. Similarly, the risk of the primary outcome and all-cause mortality (HR 95% CI) associated with engaging in MPA for ≥15 min/day, relative to <15 min/day was 0.76(0.63-0.93; p=0.008) and 0.80(0.62-1.02; p=0.066), respectively. Conclusion: Among individuals with hypertension from the SPRINT study, VPA and MPA at a threshold of ≥1sessions/month and MPA of ≥15 min/day respectively, were both associated with a lower risk for cardiovascular events, and VPA was also associated with a reduced risk for all-cause mortality. Further studies are required to identify the optimal volume and intensity of PA in high-risk hypertension.